A Risk-Based Permitting Process for the Managed Movement of Animals and Products of Animal Origin as a Tool for Disease Management - Umber, Jamie; Culhane, Marie; Cardona, Carol; Goldsmith, Timothy (Frontiers in Veterinary Science, 2019)
During a foreign animal disease (FAD) outbreak, in addition to detecting, controlling, containing, and eradicating the FAD, one of the goals of response in the United States (US), and many other countries, is to allow the managed movement of non-infected animals and non-contaminated animal products from within FAD control areas to facilitate continuity of business (COB). Permits issued by government authorities are the mechanism by which such managed movements are allowed in the US, resulting in permitted movements. The overall purpose of issuing permits during an outbreak is to minimize the risk of disease spread while still allowing movement of products or animals; thus, the risk associated with each permitted movement must be considered. Currently, there are federal guidelines for the various permit types and purposes. These guidelines state that permits should be “based on science and risk-based information.” However, federal guidelines with specific procedures to determine risk are not readily available nor do they explicitly enumerate measures to assist regulatory authorities in using risk to guide decisions to grant permitted movement or deny a request to move. Although some pro-active risk assessments (RAs) have been conducted to determine risk of moving certain animals and their products, there will always be animal and product movements for which no pro-active RAs exist. We present here a process description of steps to conduct risk-based permitting with appropriate resource allocation to permitting by industry and regulatory authorities during an FAD outbreak.